2002
DOI: 10.1002/app.11465
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive mixtures of polyaniline and EPDM rubber: Chemical, thermal, and morphological characterization

Abstract: ABSTRACT:A new route for blending polyaniline (PAni) and EPDM rubber was devised with maleic anhydride as a compatibilizer precursor. Rubber matrices containing ammonium peroxidisulfate and dodecyl benzene sulfonic acid were cast from organic solvents. Exposure to the monomer vapors allowed the chemical polymerization of aniline. The influence of PAni and the compatibilizer on the thermal properties, chemical structure, electrical conductivity, and morphology of the mixtures was observed with differential scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
12

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 42 publications
(58 reference statements)
1
3
0
12
Order By: Relevance
“…The small shift in the peak position and the intensity were due to the different dopant levels of the resulting PANi. We observed that the SO peak in the blends was slightly shifted, and the same was observed for SO 3 H. This clearly indicated that hydrogen bonding21, 22 took place in the sulfonyl group of SPES and the amine groups of PANi, shown in Figure 4; intermolecular interaction was observed in the blends. This confirmed the fact that PANi was dispersed as an interpenetrating network in the SPES matrix.…”
Section: Resultssupporting
confidence: 65%
“…The small shift in the peak position and the intensity were due to the different dopant levels of the resulting PANi. We observed that the SO peak in the blends was slightly shifted, and the same was observed for SO 3 H. This clearly indicated that hydrogen bonding21, 22 took place in the sulfonyl group of SPES and the amine groups of PANi, shown in Figure 4; intermolecular interaction was observed in the blends. This confirmed the fact that PANi was dispersed as an interpenetrating network in the SPES matrix.…”
Section: Resultssupporting
confidence: 65%
“…Peaks at 2919 and 2859 cm −1 represent C‐H vibration mode in EPDM 36 . Peak at 742 cm −1 is due to the angular deformation of the C‐H 2 linkage in the EPDM chain 37 . Stretching vibration at 1459 and 1374 cm −1 states that C‐H 2 bending and angel deformation of C‐H 3 group in EPDM chain 38 .…”
Section: Resultsmentioning
confidence: 99%
“…36 Peak at 742 cm À1 is due to the angular deformation of the C-H 2 linkage in the EPDM chain. 37 Stretching vibration at 1459 and 1374 cm À1 states that C-H 2 bending and angel deformation of C-H 3 group in EPDM chain. 38 Figure 7B shows FTIR-ATR spectrums of different EPDM composites.…”
Section: Transmission Electron Microscopy Analysismentioning
confidence: 99%
“…Domenech et al [20] found that MAH forms covalent bonds with the PANI backbone in PANI/DBSA complex. Our studies show that the drop in conductivity is significant with MAH-functionalized polyethylene as compatibilizer.…”
Section: Resultsmentioning
confidence: 99%